137Cs and 90Sr in the water of the ChNPP cooling pond - V. V. Kanivets; S. I. Kireev; G. V. Laptev; O. I. Nasvit; S. M. Obrizan (Ядерна фізика та енергетика)
Results of long-term observations on 137Cs and 90Sr concentration in water mass of the ChNPP Cooling Pond are presented. Drastic transformation of the intrinsic trend in changes with time of averaged radionuclides con-tent in water is clearly demonstrated alongside with the spatial heterogeneity of radioactive contamination of water body. The cycling character of seasonal changes of 137Cs activity concentration in water is being linked to hydrochemical, temperature and oxygen regimes of the Cooling Pond.